PENGARUH EDUKASI GIZI BERBASIS E-BOOK “BEBMIA” TERHADAP PENGETAHUAN, SIKAP, DAN KEPATUHAN KONSUMSI TTD SISWI SMAN 2 PALANGKA RAYA: Effect of the “BEBMIA” e-book–Based Nutrition Education on Knowledge, Attitudes, and Iron Supplement Adherence among Female Students at SMAN 2 Palangka Raya - Nila Susanti; Vilony Natalia Nayar; Harlyanti Muthma'innah Mashar; Aditya Suryaputra (Poltekkes Kemenkes Yogyakarta, 2026)
Anemia is a risk factor for stunting which is also a nutritional problem in Indonesia. The stunting reduction acceleration program is a priority in Indonesia. In this specific intervention there are several target groups including female adolescents. This study aims to analyze the effect of the